Neuroprotective effects of Danshensu on rotenone-induced Parkinson's disease models in vitro and in vivo - Tian Wang; Cuiting Li; Bing Han; Zhenhua Wang; Xiaoyu Meng; Leiming Zhang; Jie He; Fenghua Fu (BMC, 2020)
Abstract Background Danshensu is an active constituent in the extracts of Danshen which is a traditional Chinese medical herb. Rotenone inhibits complex I of the mitochondrial electron transport chain in dopaminergic neurons leading to glutathione (GSH) level reduction and oxidative stress. The aim of this study is to investigate neuroprotective effects of Danshensu on rotenone-induced Parkinson's disease (PD) in vitro and in vivo. Methods In vitro, SH-SY5Y human neuroblastoma cell line was pretreated with Danshensu and challenged with rotenone. Then the reactive oxygen species (ROS) production was assayed. In vivo, male C57BL/6 mice were intragastrically administered with Danshensu (15, 30, or 60 mg/kg), followed by oral administration with rotenone at a dose of 30 mg/kg. Pole and rotarod tests were carried out at 28 d to observe the effects of Danshensu on PD. Results Danshensu repressed ROS generation and therefore attenuated the rotenone-induced injury in SH-SY5Y cells. Danshensu improved motor dysfunction induced by rotenone, accompanied with reducing MDA content and increasing GSH level in striatum. Danshensu increased the number of TH positive neurons, the expression of TH and the dopamine contents. The expressions of p-PI3K, p-AKT, Nrf2, hemeoxygenase (HO-1), glutathione cysteine ligase regulatory subunit (GCLC), glutathione cysteine ligase modulatory subunit (GCLM) were significantly increased and the expression of Keap1 was decreased in Danshensu groups. Conclusions The neuroprotective effects of Danshensu on rotenone-induced PD are attributed to the anti-oxidative properties by activating PI3K/AKT/Nrf2 pathway and increasing Nrf2-induced expression of HO-1, GCLC, and GCLM, at least in part.